2022
DOI: 10.1161/hypertensionaha.121.18916
|View full text |Cite
|
Sign up to set email alerts
|

Evidence From Human Placenta, Endoplasmic Reticulum–Stressed Trophoblasts, and Transgenic Mice Links Transthyretin Proteinopathy to Preeclampsia

Abstract: Background: We have demonstrated that protein aggregation plays a pivotal role in the pathophysiology of preeclampsia and identified several aggregated proteins in the circulation of preeclampsia patients, the most prominent of which is the serum protein TTR (transthyretin). However, the mechanisms that underlie protein aggregation remain poorly addressed. Methods: We examined TTR aggregates in hypoxia/reoxygenation-exposed primary human … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 61 publications
(156 reference statements)
1
14
0
Order By: Relevance
“…In patients with PE, the placenta is defective and trophoblast cells are hypoxic ( 166 ), which leads to increased secretion of HMGB1 by hypoxic trophoblastic tissues. The secretion of HMGB1 induces endothelial cell hyperpermeability via the TLR4/caveolin-1 pathway.…”
Section: Hmgb1-targeted Therapeutic Agentsmentioning
confidence: 99%
“…In patients with PE, the placenta is defective and trophoblast cells are hypoxic ( 166 ), which leads to increased secretion of HMGB1 by hypoxic trophoblastic tissues. The secretion of HMGB1 induces endothelial cell hyperpermeability via the TLR4/caveolin-1 pathway.…”
Section: Hmgb1-targeted Therapeutic Agentsmentioning
confidence: 99%
“…TTR, as one of the most prominent aggregated proteins in preeclamptic mothers’ circulation, serves as a marker of preeclampsia. In vitro, TTR aggregations on human trophoblast are shown to be induced by endoplasmic reticulum stress inducers and autophagy disruptors, indicating that TTR could be a contributor to preeclampsia pathophysiology (Cheng et al, 2022). In line with this data, several human mutations in the TTR gene have been associated with amyloid TTR disease, resulting in systemic deposition of conglomerates of TTR in the extracellular space with variable degrees of disability (Conceição et al, 2019).…”
Section: Th Metabolism In the Placentamentioning
confidence: 99%
“…Our prior studies have demonstrated that TTR misfolding and aggregation contribute to the pathogenesis of preeclampsia (PE), a pregnancy-specific, multifactorial syndrome characterized by hypertension after 20 weeks of gestation [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. PE is a leading cause of maternal and fetal morbidity and mortality, affecting 3–8% of all pregnancies worldwide [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Despite extensive investigations, the etiology of PE remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent studies have revealed a robust deposition of TTR aggregates in trophoblasts in the PE placenta. This is thought to be caused by excessive endoplasmic reticulum (ER) stress, exhausted unfolded protein response, and impaired autophagy-lysosomal machinery [ 17 , 18 ]. Furthermore, transgenic mice over-expressing human TTR experienced TTR aggregate accumulation in the placenta, PE-like features, and increased production of sFlt-1 and soluble endoglin [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation